Serologic Evaluation of MERS Screening Strategy for Healthcare Personnel During a Hospital-Associated Outbreak. (14th November 2016) - Ko, Jae-Hoon; Lee, Ji Yeon; Baek, Jin Yang; Seok, Hyeri; Park, Ga Eun; Lee, Ji Yong; Cho, Sun Young; Ha, Young Eun; Kang, Cheol-In; Kang, Ji-Man; Kim, Yae-Jean; Kang, Eun-Suk; et al.
Abstract : To evaluate the appropriateness of the screening strategy for healthcare personnel (HCP) during a hospital-associated Middle East Respiratory Syndrome (MERS) outbreak, we performed a serologic investigation in 189 rRT-PCR–negative HCP exposed and assigned to MERS patients. Although 20%–25% of HCP experienced MERS-like symptoms, none of them showed seroconversion by plaque reduction neutralization test (PRNT). Infect Control Hosp Epidemiol 2017;38:234–238